The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/ac020386r
|View full text |Cite
|
Sign up to set email alerts
|

Polysodium N-Undecanoyl-l-leucylvalinate:  A Versatile Chiral Selector for Micellar Electrokinetic Chromatography

Abstract: Dipeptide micelle polymers are a new class of polymeric surfactants of which the polysodium undecanoyl-L-leucylvalinate (poly-L-SULV) was found to be a broadly applicable chiral selector for micellar electrokinetic chromatography. This negatively charged dipeptide micelle polymer is a high molecular weight compound with large countercurrent mobility, zero critical micelle concentration, low aggregation number, and high solubility in water or water-organic solvents. In an extensive chiral screening program, ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 27 publications
(41 reference statements)
4
69
0
Order By: Relevance
“…In addition to the surfactant head group, effects of hydrocarbon chain length of both conventional surfactants [11][12][13][14] and polymeric surfactants [15][16][17][18][19][20][21] on chemical selectivity have been investigated. While the effects of the polar head group of amino acid-based polymeric surfactants have received considerable attention, these studies have been limited to chiral separations [22][23][24][25][26][27]. In 1997, Shamsi et al [28] employed a poly(sodium N-undecenoyl-L-dipeptide) surfactant with two chiral centers to achieve improved chiral separations in MEKC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the surfactant head group, effects of hydrocarbon chain length of both conventional surfactants [11][12][13][14] and polymeric surfactants [15][16][17][18][19][20][21] on chemical selectivity have been investigated. While the effects of the polar head group of amino acid-based polymeric surfactants have received considerable attention, these studies have been limited to chiral separations [22][23][24][25][26][27]. In 1997, Shamsi et al [28] employed a poly(sodium N-undecenoyl-L-dipeptide) surfactant with two chiral centers to achieve improved chiral separations in MEKC.…”
Section: Introductionmentioning
confidence: 99%
“…This usually provides higher efficiencies and rapid analysis. They have, over the years, been extensively used in a BGE [74][75][76][77][78][79][80], in a polyelectrolyte multilayer coating [63,74,[81][82][83], and in a CE-MS system [84][85][86].…”
Section: Methods Development and Validationmentioning
confidence: 99%
“…As far as the chiral selector is concerned, different polymeric surfactants were examined, such as poly(sodium N-undecanoyl-L-leucinate) (poly-L-SUL), poly(sodium N-undecanoyl-LL-leucyl-leucinate) (poly-LL-SULL), poly(sodium N-undecanoyl-LL-leucyl-valinate) (poly-LL-SULV), poly(sodium N-undecanoyl-L-valinate) (poly-L-SUV), poly(sodium Nundecanoyl-L-valyl-glycinate) (poly-L-SUVG), poly(sodium N-undecanoyl-LL-alanylvalinate) (poly-LL-SUAV), poly(sodium N-undecanoyl-LL-leucyl-alanate) (poly-LL-SULA), and poly(sodium N-undecanoyl-LL-valyl-valinate) (poly-LL-SUVV). The polymeric surfacant poly-LL-SULV, which has shown the best chiral discrimination ability for a number of pharmaceutical compounds [80], was the first to be examined in different concentrations. The concentration of 0.075% w/v was chosen as the optimum, based on analysis time, efficiency and resolution.…”
Section: Methods Development and Validationmentioning
confidence: 99%
“…An extensive study of the performance of LL-leucyl-valinate showed that the chiral polymer was able to provide some level of resolution for 58 of 75 cationic, neutral, and anionic racemic compounds [33]. Anionic compounds were more difficult to resolve, presumably due to ionic repulsion.…”
Section: Polymerized Amino Acid Surfactantsmentioning
confidence: 99%